2019
DOI: 10.1093/advances/nmz008
|View full text |Cite
|
Sign up to set email alerts
|

Status on the Scale Development to Measure Water Insecurity Experiences at the Household Level: A Narrative Review

Abstract: Adequate and safe water is critical in promoting all 3 pillars of food security. Hence, ensuring availability of water for all is one of the 2030 Sustainable Development Goals. To monitor progress of this goal and understand the role of water in addressing food insecurity, development of a household-level water insecurity scale has become very critical. As such, using the following concept of water insecurity: inconsistent access to sufficient amount of safe and clean water for active and healthy life, several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Overlapping with the quantity domain, women also identified the issue of not being able to drink water because of its taste. In some of the other reported scales, water insecurity was associated with drinking bad quality water [ 6 ]. For instance, in the scale by Tsai et al (2016) in rural Uganda, two items were included representing poor quality of drinking water, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Overlapping with the quantity domain, women also identified the issue of not being able to drink water because of its taste. In some of the other reported scales, water insecurity was associated with drinking bad quality water [ 6 ]. For instance, in the scale by Tsai et al (2016) in rural Uganda, two items were included representing poor quality of drinking water, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the findings from previous water access-related studies conducted in the study area [ 25 , 26 ] and existing household water insecurity scales literature [ 6 ], questions for the FGDs were designed.…”
Section: Methodology Of the Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…When the availability of water was limited, household members either drank less water than they felt they should, drank unclean water, or as a last resort borrowed drinking water from a neighbor. Additionally, in a review of recently developed household-level water insecurity scales, it was found that skipping drinking or reducing water intake was one of the strongest scale items of water insecurity assessment [27]. Hence, a link between limited water access and food insecurity is also occurring by reduced daily intake of water.…”
Section: Discussionmentioning
confidence: 99%